HLA‐B leader genotypes in a clinical population - Balgansuren, Gansuvd; Sprague, Maggie; Peterson, Paula; Shenavar, Yasaman; Ng, Ada; Regen, Lois; Shelton, Nakita; Petersdorf, Effie (HLA, 2023)
The −21 dimorphism in the leader sequences of HLA‐B exon 1 is associated with risk of graft‐versus‐host disease (GVHD), relapse and overall survival after unrelated donor hematopoietic cell transplantation (HCT), haploidentical HCT and cord blood transplantation. Consideration of the leader dimorphism in the prospective selection of allogeneic donors for HCT may help to lower risks for patients, but requires understanding of the frequencies of the leader in patients and candidate transplant donors. We defined the frequencies of the HLA‐B leader, and its association to HLA‐B Bw4/Bw6 and C1/C2 KIR epitopes. Sequence variants of rs1050458 of exon 1 position −21 for 11,126 haplotypes were analyzed from high resolution HLA typing of over 5500 study subjects. HLA typing was performed by TruSight/AlloSeq NGS and analyzed using TruSight/AlloSeq Assign software. HLA‐B Bw4/Bw6 and C1/C2 KIR epitopes were defined based on established sequence alignments and nomenclature. Alleles at rs1050458 of HLA‐B exon 1 were validated as dimorphic: rs1050458‐C or ‐T variants encoding threonine (T) or methionine (M) at anchor position 2 (P2) of nonameric HLA‐B leader peptides, respectfully. No additional variants were observed. Among study subjects, 70% of HLA‐B haplotypes encoded T‐leader and 30% encoded M‐leader sequences. The genotype frequencies of TT, MT, and MM were consistent among patient, related, and unrelated donor groups. The associations of M/T leader, Bw4/Bw6, and C1/C2 enhanced understanding of the Class I features involved in the innate immune response. A population of patients and transplant donors confirms the rs1050458 leader dimorphism and its association with HLA‐B Bw4/Bw6 and C1/C2 KIR features.